The Moderating Role of Customer Experience on the Influence of Brand Image and Price Perception Toward Purchase Decision of Hamlin Products - Kadek Dinda Ayu Puspawangi; I Nyoman Sunarta (Sean Institute, 2025)
This study aims to analyze the effect of brand image and price perception on purchase decisions of Hamlin products, with customer experience as a moderating variable. The research was conducted online by distributing questionnaires to consumers of Hamlin products in Bali, one of the rapidly growing markets in fashion trends and social media usage. Although Hamlin’s distribution center is located in Jakarta, Bali was chosen as the research focus due to its consumers’ unique characteristics, including high sensitivity to brand image and price perception, responsiveness to social media trends, and adaptability to the fusion of tradition and modernity in fashion. This research uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) through the SmartPLS 4.0 application. The sample consisted of 160 respondents selected using purposive sampling individuals who had purchased Hamlin products. Data were collected through online questionnaires. The results show that brand image has a positive and significant effect on purchase decisions, and price perception also has a positive and significant effect on purchase decisions. However, customer experience does not moderate the effect of brand image and price perception on purchase decisions. This indicates that consumers’ previous experiences with Hamlin products have not strengthened the relationship between brand image or price perception and their purchasing decisions. The findings support the Theory of Planned Behavior (TPB), where attitude formation based on positive brand image and fair price perception strongly influences consumer decision-making. The absence of a moderating effect suggests that Hamlin’s consumers base their purchase decisions primarily on current perceptions rather than past experiences. The results provide managerial implications for Hamlin to enhance brand image and maintain perceived price fairness while improving customer experience to foster greater purchase confidence and loyalty.